Global Voices in Higher Education 2017
DOI: 10.5772/intechopen.68511
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Research and Knowledge Exchange in the Science Undergraduate Curriculum: Embedding Employability Through Research-Involved Teaching

Abstract: The aim of this chapter is to give an overview of how engaging undergraduate students with research and research-related activities can be used to enrich their learning experience and enhance their employability prospects. There are two specific challenges in producing industry-ready science graduates: providing students with relevant subject specific and transferable skills and knowledge, and to provide them with appropriate industry engagement. The science undergraduate curriculum at Canterbury Christ Church… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…In the literature, a range of approaches have been explored for embedding employability in the curricula (Harvey et al, 2017;Shivoro et al, 2017). Below we discuss the key models.…”
Section: Existing Models and Framework Of Embedding Employabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a range of approaches have been explored for embedding employability in the curricula (Harvey et al, 2017;Shivoro et al, 2017). Below we discuss the key models.…”
Section: Existing Models and Framework Of Embedding Employabilitymentioning
confidence: 99%
“…Embedding employability through research-involved teaching: In this model, undergraduates are provided with research experiences, which has shown to prepare them for increasingly complex careers equipping them transferrable generic skills best acquired through research (Harvey et al, 2017).…”
Section: Work-based or Work-related Learning In Parallel With The Cur...mentioning
confidence: 99%
“…One route leads to the development of academic expertise in centres of excellence which governs the perceived strength of the academic institution. The second route arrives at the perceived strength of an academic institution through the quality of teaching and skills development influencing graduate employability (Clarke, 2018; Harvey et al, 2017; Osmani et al, 2015), determining the attractiveness of a university to student applicants (Andrews and Russell, 2012; Shah, et al, 2013). The level of student capability then in turn enhances the perceived strength of the academic institution.…”
Section: A Systems Model Of Regional Innovation Systemsmentioning
confidence: 99%
“…In higher education levels, students start to consume a rising proportion of their valuable time for researching. Typically, university students study one or more semesters in labs or practically, although the kinds of activity and type of supervising vary considerably (Harvey et al, 2017).…”
Section: Integrating Research Into Teaching Higher Educationmentioning
confidence: 99%